Carbapenemase-Producing Gram-Negative Bacteria from American Crows in the United States - Kutilova, Iva; Valcek, Adam; Papagiannitsis, Costas C; Cejkova, Darina; Masarikova, Martina; Paskova, Veronika; Davidova-Gerzova, Lenka; Videnska, Petra; Hrabak, Jaroslav; Literak, Ivan; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2020)
Wild corvids were examined for the presence of carbapenemase-producing Gram-negative bacteria in the United States. A total of 13 isolates were detected among 590 fecal samples of American crow; 11 Providencia rettgeri isolates harboring blaIMP-27 on the chromosome as a class 2 integron gene cassette within the Tn7 transposon, 1 Klebsiella pneumoniae ST258 isolate carrying blaKPC-2 on a pKpQIL-like plasmid as a part of Tn4401a, and 1 Enterobacter bugandensis isolate with blaIMI-1 located within EcloIMEX-2.
Keywords: Microbial Sensitivity Tests; Enterobacter; Spojené státy americké; wild birds; IMI; IMP-27; Crows; KPC; Klebsiella pneumoniae; mikrobiální testy citlivosti; Klebsiella Infections; antibakteriální látky; zvířata; vrány; plazmidy; United States; bakteriální proteiny; infekce bakteriemi rodu Klebsiella; carbapenemase; beta-laktamasy; Anti-Bacterial Agents; Providencia rettgeri; Bacterial Proteins; beta-Lactamases; Animals; Plasmids; Providencia